Epigenome-Wide Association Study of Wellbeing. (1st December 2015) - Baselmans, Bart M. L.; van Dongen, Jenny; Nivard, Michel G.; Lin, Bochao D.; Consortium, BIOS; Zilhão, Nuno R.; Boomsma, Dorret I.; Bartels, Meike
Abstract : Wellbeing (WB) is a major topic of research across several scientific disciplines, partly driven by its strong association with psychological and mental health. Twin-family studies have found that both genotype and environment play an important role in explaining the variance in WB. Epigenetic mechanisms, such as DNA methylation, regulate gene expression, and may mediate genetic and environmental effects on WB. Here, for the first time, we apply an epigenome-wide association study (EWAS) approach to identify differentially methylated sites associated with individual differences in WB. Subjects were part of the longitudinal survey studies of the Netherlands Twin Register (NTR) and participated in the NTR biobank project between 2002 and 2011. WB was assessed by a short inventory that measures satisfaction with life (SAT). DNA methylation was measured in whole blood by the Illumina Infinium HumanMethylation450 BeadChip (HM450k array) and the association between WB and DNA methylation level was tested at 411, 169 autosomal sites. Two sites (cg10845147, p = 1.51 * 10 −8 and cg01940273, p = 2.34 * 10 −8 ) reached genome-wide significance following Bonferonni correction. Four more sites (cg03329539, p = 2.76* 10 −7 ; cg09716613, p = 3.23 * 10 −7 ; cg04387347, p = 3.95 * 10 −7 ; and cg02290168, p = 5.23 * 10 −7 ) were considered to be genome-wide significant when applying the widely used criterion of a FDR q value < 0.05. Gene ontology (GO) analysis highlighted enrichment of several central nervous system categories among higher-ranking methylation sites. Overall, these results provide a first insight into the epigenetic mechanisms associated with WB and lay the foundations for future work aiming to unravel the biological mechanisms underlying a complex trait like WB.